Low health literacy associated with higher medication costs in patients with type 2 diabetes mellitus: Evidence from matched survey and health insurance data. Issue 12 (December 2015) - Mantwill, Sarah; Schulz, Peter J.
Highlights: Lower levels of health literacy are associated with higher medication costs. Patients with limited health literacy have higher healthcare costs. Results suggest that health literacy influences medication use. Supervision of medication regimen crucial for those with limited health literacy. Abstract: Objective: Studies have shown that people with lower levels of health literacy create higher emergency, inpatient and total healthcare costs, yet little is known about how health literacy may affect medication costs. This cross-sectional study aims at investigating the relationship between health literacy and three years of medication costs (2009–2011) in a sample of patients with type 2 diabetes. Methods: 391 patients from the German-speaking part of Switzerland who were insured with the same health insurer were interviewed. Health literacy was measured by a validated screening question and interview records were subsequently matched with data on medication costs. A bootstrap regression analysis was applied to investigate the relationship between health literacy and medication costs. Results: In 2010 and 2011 lower levels of health literacy were significantly associated with higher medication costs ( p < .05). Conclusion: The results suggest that diabetic patients with lower health literacy will create higher medication costs. Practice implications: Besides being sensitive towards patients' health literacy levels, healthcare providers may have to take into account its potential impact on patients' medication regimen, misuse and healthcare costs.